Implementation of Competency-Based Performance Appraisal System to Ensure Accuracy and Effectiveness of Employee Evaluation - Putra, Arif Rachman (Journal of Social Science Studies, 2021)
Competency-based performance appraisal systems have become an increasingly adopted approach in human resource management to improve the accuracy of employee evaluations and support the achievement of organizational goals. This study aims to analyze the effectiveness of these systems to improve the quality of performance-based decision-making and identify optimal strategies for developing competency indicators that are aligned with organizational needs. Using a literature study approach, this research examines various competency-based performance assessment models, the role of technology to support the implementation of this system, and the challenges faced in its application. The results show that a competency-based system allows organizations to develop more objective and data-driven evaluation methods that increase transparency and reliability in the assessment process. The integration of technologies, such as artificial intelligence and data analytics, is proven to contribute to reducing bias and increasing efficiency in performance evaluation. Developing effective competency indicators requires a data-driven approach, machine learning modeling, and integration with the organization's business strategy. Challenges in implementing the system include adapting to the changing needs of the industry and the need for training of assessors to ensure an accurate evaluation process. Therefore, organizations need to develop flexible, technology-based and employee development-oriented evaluation mechanisms to ensure the sustainability of an effective competency-based assessment system.